Endurance Capacity and Cardiorespiratory Responses in Sedentary Females During Different Phases of Menstrual Cycle - Bandyopadhyay, A; Dalui, R (Kathmandu University Medical Journal, 2014)
Background Alteration in physical work capacity of females during different phases of menstrual cycle has been reported in different populations. Pertinent data is unavailable in Eastern Indian population. Objectives The present study was aimed to determine the endurance capacity and cardiorespiratory responses during different phases of menstrual cycle in young sedentary females of Eastern region of India. Methods Forty five unmarried young healthy sedentary females (21–25 years) were recruited in the present investigation. Duration of their menstrual cycle was 28–30 days. Cardiorespiratory parameters including the endurance capacity was determined by treadmill running with constant monitoring of heart rate by Polar heart rate monitor. Results The pre-exercise heart rate was significantly higher (P